Cognitive behavior therapy intervention on adolescents to decrease anxiety problem study: the role of serotonin - Nancye, Pandeirot Marjory; Husni, Amin; Sawitri, Dian Ratna (International Journal of Public Health Science (IJPHS), 2024)
The existence of demands that occur simultaneously causes some adolescents to be unable to adapt properly, especially the condition of adolescents who experience changeable emotions, are unstable, easily stressed, feel anxious, depressed, and feel helpless. Cognitive behavior therapy (CBT) is a form of psychotherapy that can be used for adolescent emotional problems. The purpose of this study is to prove that CBT interventions can increase serotonin levels and reduce adolescent anxiety levels. The research population is adolescents with anxiety problems in the city of Surabaya. The research sample is 32 respondents with techniques systematic sampling. Inclusion criteria include: i) adolescents aged 12–18 years, ii) experiencing mental emotional anxiety problems as measured by a score with self-reporting questionnaire (SRQ-29), and iii) being willing to participate in the research and get permission from parents. Data collection using an instrument in the form of a Taylor Manifest Anxiety Scale (TMAS). The data have been analyzed by the Wilcoxon test. The results show that there were significant differences in serotonin levels and anxiety levels before and after the intervention given CBT. The average value of serotonin levels in the posttest was higher than the pretest (p=0.001) and the average value of anxiety levels in the posttest was lower than the pretest (p=0.043) indicating that giving CBT interventions was able to significantly reduce anxiety levels. CBT interventions are proven to increase serotonin levels and reduce adolescent anxiety levels. By changing the form of thought and the resulting consequences, the intensity of the subject's anxiety decreases.